VERBA PANCAINDRA DALAM BAHASA DAYAK KANAYATN - Meriana, Meriana; Sulissusiawan, Ahadi; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study focused on observing the sensory verb in the Dayak Kanayatn language. This study has four specific problems, namely (1) review the sensory verb in the Dayak Kanayatn language, (2) review the meaning of the sensory verb in the Dayak Kanayatn language, and (3) review the morphological processes of deep the sensory verb in the Dayak Kanayatn language. The research method used in this study was descriptive with a qualitative form. The data sources used in this study were data that have been obtained from the gospels of Matthew, Mark, Luke, and John. Then to complete the data, researchers prioritized the data obtained from informants, namely speakers of native language Dayak Kanayatn. The technique of collected data, reading and grouping each of the five sensory verbs obtained, and describing the sensory verbs that have been obtained. The results of the study, namely there were free basic verbs, there were 9 senses of seer, 2 senses of the listener, 1 sense of sniffer, 3 senses of taste, and 2 sense of touch. Derivative verbs have 35 senses of seer, 10 senses of listeners, 7 senses of smell, 10 senses of taste, and 8 senses of touch.Â Keywords: Morphologies, Scriptures, Senses, Verbs